PD-L1 Expression in Mismatch Repair-deficient Endometrial Carcinomas, Including Lynch Syndrome-associated and MLH1 Promoter Hypermethylated Tumors. (March 2017) - Sloan, Emily A.; Ring, Kari L.; Willis, Brian C.; Modesitt, Susan C.; Mills, Anne M.
Abstract : Mismatch repair (MMR)-deficient endometrial carcinomas (ECs) bearing Lynch syndrome (LS)-associated germline mutations or sporadic MLH1 promoter hypermethylation ( MLH1hm ) are highly immunogenic and may represent excellent candidates for therapies targeting the programmed cell death (PD)/programmed cell death ligand-1 (PD-L1) immune checkpoint pathway. This study evaluates PD-L1 expression in MMR-deficient ECs including LS-associated and MLH1hm cases, in comparison with MMR-intact tumors. Immunohistochemistry for PD-L1/CD274 was performed on 38 MMR-deficient and 29 MMR-intact ECs. Staining was scored in the tumor and the peritumoral immune compartment. The majority of MMR-deficient tumors were PD-L1 positive (53%) in at least a subset of tumor cells. LS-associated tumors were more likely to be PD-L1 positive relative to MLH1hm tumors (70% vs. 33%, P =0.05). Only 10% of MMR-intact ECs demonstrated any tumoral PD-L1 expression; this was significantly lower than was observed in MMR-deficient tumors ( P =0.0005). When reviewed by histologic grade, PD-L1 expression remained highest in LS-associated ECs followed by MLH1hm and MMR-intact carcinomas, respectively. The MMR immunohistochemical pattern most uniformly associated with PD-L1 expression was MSH6 loss. Immune PD-L1 expression was seen in 100% of MMR-deficient and 66% of MMR-intact cases. This study represents the first to characterize differences in PD-L1 expression between LS-associated and MLH1hm endometrial cancers. It demonstrates that tumoral PD-L1 expression is more common in LS-associated endometrial cancers relative to MLH1hm and MMR-intact tumors, although sporadic cancers often show PD-L1 positive immune staining. These data suggest that MMR deficiency may be a better predictor of response to PD-1/PD-L1 inhibitor therapy than tumor grade in EC, and that potential benefit may vary based on the molecular mechanism of MMR defects.